Available phosphorus from phosphate extracted from swine wastewater for poultry - Fernando de Castro Tavernari; Airton Kunz; Vivian Feddern; Ricardo Steinmetz; Paola de Azevedo Mello; Valderi Luiz Dressler (Ciência Rural)
ABSTRACT: This research evaluated phosphorus availability, from phosphate extracted from swine wastewater, in broilers. Phosphorus inorganic contaminants were determined. Afterward, an experiment was carried out with 2,520 broilers, divided in randomized blocks, 9 treatments (0, 0.5, 1.0, 1.5, and 2.0g/kg P from phosphate extracted from swine wastewater and 0.5, 1.0, 1.5, and 2.0g/kg P from dicalcium phosphate), 10 repetitions and 28 birds per experimental unit. The animals’ age was from 1 to 14 days old, which were housed in boxes and fed ad libitum (water and feed). At 14 days, 3 birds per experimental unit were slaughtered to evaluate tibia-breaking strength. Data were submitted to analysis of variance and regression. Phosphorus biological availability from the commercial source was calculated by the ratio of the regression coefficients, considering the phosphorus from dicalcium phosphate as 100% available. The inorganic contaminants showed that concentrations in phosphate extracted from swine wastewater in relation to dicalcium phosphate are similar or at lower concentration levels. The phosphorus availability of 32.53% was observed for simple linear equation and 31.38% for multiple linear equation. Phosphate advantages from swine wastewater are reflected in the environmental issue, that is, free of contamination (inorganic metals) and less amount disposed in the environment. The outcomes of this research indicated no pathogens (Salmonella sp. and E. coli) in the phosphate extracted from swine wastewater applied in broilers, and phosphorus average availability of 31%.